STRATEGI BRANDING DALAM MENINGKATKAN DAYA TARIK SEKOLAH : STUDI KASUS DI SMA NEGERI 3 KOTA JAMBI - Zarastri, Ririn; Ardhani, Deliana; Supriadi, Sudawan; Chairunnisa, Chairunnisa (Jurnal Pendidikan Ekonomi, 2024)
School branding is an increasingly important strategy in the context of competitive education, particularly in the digital era. This study aims to explore school branding strategies to enhance the appeal and quality of education, with a case study at SMA Negeri 3 Kota Jambi. Through the implementation of the Kurikulum Merdeka (Freedom Curriculum), which integrates academic and non-academic development, the school has built a positive image that strengthens its reputation and attracts prospective students. The research employs a qualitative approach using in-depth interviews with the vice principal of curriculum and students. The findings reveal that effective branding strategies do not only focus on visual identity but also emphasize educational excellence and collaboration with various stakeholders. These strategies create significant appeal within the community, positioning the school as a leader in the competitive landscape of educational institutions